SUPPLY ANALYSIS FOR MAIZE IN OYO AND OSUN STATES OF NIGERIA: Life Science-Agriculture Science - OLADEJO; ADEFEMI, JOANA; LADIPO; OLASUPO O. (International Journal of Life Science and Pharma Research, 2012)
This research analyzed the quantity of maize supplied and factors determining such quantity with a focus on maize farmers in Oyo and Osun States of Nigeria. Multistage random sampling technique was employed to sample four hundred maize farmers for the study. A structured interview schedule was used to collect primary data from the respondents. Data were obtained on socio-economic characteristics of respondents, production and marketing practices, prices and costs. Data collected were analyzed using descriptive statistics and estimation of Cobb-Douglas regression model. Data analysis revealed that the mean age for the sampled farmers was 46 years and that more than half of the respondents were literate. The summary of marital status distribution of respondents showed that about ninety-three percent of the interviewed farmers were married while the mean household size was 7. Distribution of sampled farmers based on major source of finance showed that 58.5percent of respondents depended on personal savings in financing their maize production activities. The result further revealed that 52 percent of the maize farmers cultivated less than two hectares of land, and that most of the respondents are low income earners, with an average annual income of #116,000.00. Regression analysis revealed the R-squared (R2 ) as 0.734. This showed that 73.4 percent of the variation in quantity of maize supplied by respondents was explained by the estimated variables. The F value of 119.767 was significant at 1percent level of significance. Data analysis showed that significant relationships exist between market factors and agricultural household supply response in the study area. The study concluded that in addition to price factor, marketing costs contribute significantly to agricultural household supply decisions, and consequently recommends that policies that reduce marketing costs should be formulated and implemented to serve as compliments to various price policies in ensuring adequate returns to farmers’ investment and stimulate expansion in food production thereby enhancing the level of food security in Nigeria